Formation, Detection, and Function of Oxygen Vacancy in Metal Oxides for Solar Energy Conversion. (31st October 2021) - Wang, Zhiliang; Lin, Rijia; Huo, Yuning; Li, Hexing; Wang, Lianzhou
Abstract: Oxygen vacancy (VO ) is one of the most common defects in metal oxides (MOs), which endow the MOs with many unique physiochemical properties. Even though VO engineering has been applied in photo(electro)catalysis, there are still significant challenges in the understanding of the formation, structure, and property of VO . The VO can be produced by treating MOs under low oxygen atmosphere or in vacuum ruled by the equilibrium of VO formation, while other types of defects can also be generated simultaneously. Identifying and distinguishing the formation and function of Vo remain highly challenging, thus the scrutiny of defect formation energy and structure of VO is significant in VO research. This review critically revisits the electronic property and structure changes of MOs upon the generation of Vo. It not only provides clues to detect VO, but also specifies the role of VO in a particular material system considering its drastic influence on light harvesting, conductivity, energy level, surface adsorption, and others. The review also presents a perspective on the future research directions toward rational control of the key aspects of Vo in MOs, namely its formation, characterization, and function, for solar energy conversion. Abstract : This article provides a critical review of the roles of oxygen vacancy in metal oxides with focuses on its formation, characterization, and function for solar energy conversion application. Recommended investigation strategies on the structure–function relationship of the oxygen vacancy are also discussed.